Kinetics of lipase-mediated synthesis of butyl butyrate in n-hexane - Paiva, Ana. L. (2011)
This paper reports experimental and modeling work concerning alcoholysis reactions between butanol and ethyl butanoate, catalyzed by Lipozymee in n-hexane, using a batch stirred system at 608C. Description of the reaction kinetics was based on a postulated multisubstrate Ping Pong Bi Bi mechanism, and appropriate rate expressions were derived for all components in the reaction medium. Simplified models were fitted by nonlinear multiresponse regression analysis to data (experimental or calculated from mass balances, as appropriate) encompassing the concentrations of free butanol, ethyl butanoate, ethanol and butyl butanoate. Finally, incremental F-tests were performed to assess the simplest model form that was able to provide a statistically good fit throughout the entire reaction time frame.